ANALOGY PROBLEM POSING FOR ELEMENTARY SCHOOL STUDENTS ON WORD PROBLEMS - Septina Risma Yunita; Mohammad Faizal Amir (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the analogy characteristics of elementary school students in proposing word problems. Analogical reasoning is a complex process that involves retrieving structured knowledge from long-term memory, representing and manipulating role-filling ties in working memory, identifying elements that play appropriate roles, generating new conclusions, and learning abstract schemes. The characteristics of analogy are categorized into four: (1) reformulation, rearrangement of information by changing the order of numbers but still paying attention to the order of mathematical operations. (2) reconstruction, Students rearrange information in the initial problem so that the problem appears different but is identical to the initial problem. (3) reproduction, the resulting product creates a new problem that is different by changing the structure of the initial problem. (4) imitation, changing the structure of the given problem by expanding the goal statement so that the initial problem becomes a step of the solution process of the new problem. Students' failure in making problem posing is included in non-reformulation, where students cannot make problem posing on word problems according to the problem structure